Karakter Sopan Santun Remaja: Pengaruh Metode Sosialisasi Orang Tua dan Kontrol Diri - Farhatilwardah, Farhatilwardah; Hastuti, Dwi; Krisnatuti, Diah (Jurnal Ilmu Keluarga dan Konsumen, 2019)
Adolescence is a period of transition from childhood to adulthood with developmental tasks to obtain social roles and emotional freedom from parents, but adolescents are still not able to control themselves properly. This study analyzes the influence of parents socialization method and self control on manners character of adolescence. This study used a cross-sectional research design. A diverse sample of both junior high school students in Cibinong sub-didtrict, Bogor District (n=187; 87 boys and 100 girls) were selected considering proportionate random sampling method to answer survey using questionnaires. The collected data was analyzed by descriptive statistic and path analysis. Findings of this study suggest that there is no difference between boys and girls in parental socialization method, self control, and manners character of adolescence. The results showed that parental socialization method (ρ=0,333) and self control (ρ=0,365) had direct positive effects on manners character of adolescence. Furthermore, parents socialization method also had indirect effect on manners character of adolescence through self control variable (ρ = 0,108). Total effect of the parental socialization method on the character manners is 44,1 percent, greater than effect of self control on the manners character ofadolescence (36,5%).